2007
DOI: 10.1037/0882-7974.22.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in recognition of emotion in lexical stimuli and facial expressions.

Abstract: Age differences in emotion recognition from lexical stimuli and facial expressions were examined in a cross-sectional sample of adults aged 18 to 85 (N = 357). Emotion-specific response biases differed by age: Older adults were disproportionately more likely to incorrectly label lexical stimuli as happiness, sadness, and surprise and to incorrectly label facial stimuli as disgust and fear. After these biases were controlled, findings suggested that older adults were less accurate at identifying emotions than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
249
9
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(297 citation statements)
references
References 61 publications
(82 reference statements)
32
249
9
7
Order By: Relevance
“…The pattern of the observed changes in emotion recognition is consistent with previous findings (e.g., Calder et al, 2003;Isaacowitz et al, 2007). The decline in responsiveness to sad and scared music replicates Laukka and Juslin's (2007) findings with older adults, and extends them by showing that this decline (a) occurs for music portraying emotions through structural features and not through expressiveness, and (b) is manifest at middle-age (ca.…”
Section: Emotion Recognition In Music and Agingsupporting
confidence: 89%
See 3 more Smart Citations
“…The pattern of the observed changes in emotion recognition is consistent with previous findings (e.g., Calder et al, 2003;Isaacowitz et al, 2007). The decline in responsiveness to sad and scared music replicates Laukka and Juslin's (2007) findings with older adults, and extends them by showing that this decline (a) occurs for music portraying emotions through structural features and not through expressiveness, and (b) is manifest at middle-age (ca.…”
Section: Emotion Recognition In Music and Agingsupporting
confidence: 89%
“…The decline in the recognition of fear started early, at around 40 years, and increased linearly with advancing age. More recently, Isaacowitz et al (2007) have also found age-related decline for fearful and angry expressions, and no decline for sad, surprised and neutral expressions. Consistent with Calder et al's results, the recognition of fear declined linearly with age.…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 91%
See 2 more Smart Citations
“…As previous research demonstrated that age (Isaacowitz et al, 2007) and gender (Donges et al, 2012) have impact on facial emotion recognition performance, their potential confounding effect was controlled for in all further analyses. Afterwards, all analyses on DFAR performance were adjusted for general facial recognition ability (BFRT).…”
Section: Statistical Analysesmentioning
confidence: 99%